Contributions of African Traditional Knowledge to Community Development Theory and Practice - Adodo, Anselm (Advances in Social Sciences Research Journal, 2023)
Africa’s capacity for developing, testing, and applying traditional knowledge is closely linked to its indigenous knowledge capacity. This paper explores the role of Indigenous knowledge in community development and the challenges associated with its integration into development theories and initiatives. Colonialism, which diminished the relevance of traditional knowledge and promoted Western development techniques, has left a legacy of dependency on Western knowledge systems. As a result, the contribution of Indigenous knowledge to community development and other developmental practices has often been overlooked. This study employs a quantitative research method based on secondary data analysis to investigate these issues. The findings highlight the significant potential of Indigenous knowledge in contributing to development efforts. However, various factors, including restrictive rules, regulations, standards, and limited funding for Indigenous knowledge research, documentation, and application, hinder its full utilisation. To address these limitations, this paper recommends the development of a clear research agenda for Indigenous knowledge, with articulated research objectives and expected outcomes. Additionally, the establishment of frameworks for validating knowledge within the educational system is proposed. These measures aim to enhance the recognition and integration of Indigenous knowledge into development practices, fostering a more holistic and culturally sensitive approach to community development.